Knowledge of general dentists in the current guidelines for emergency treatment of avulsed teeth and dental trauma prevention - Oliveira de Vasconcellos, Luis Gustavo [UNESP]; Brentel, Aline Scalone [UNESP]; Vanderlei, Aleska Dias [UNESP]; Reis de Vasconcellos, Luana Marotta [UNESP]; Valera, Marcia Carneiro [UNESP]; Maximo de Araujo, Maria Amelia [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
A high prevalence of dental trauma exists and its effects on function and esthetics deserve the attention of general dentists. The aim of this study was to assess the level of general dental practitioners' (GDPs) knowledge about guidelines for dental avulsion and its prevention using a questionnaire. The 21-item questionnaire was distributed among 264 GDPs and the survey was realized between August-November 2006. The data obtained were statistically analyzed using descriptive analysis and Pearson's Chi-square test to determine associations between knowledge regarding emergency treatment and dentists from public or private dental schools and years of experience. The results showed that the participants exhibited appropriate knowledge concerning procedures in cases of tooth avulsion and its prevention. The number of correct answers was low in relation to recommended treatment at the site of injury. Storage medium, preparation of the alveolus and splint time for receiving the avulsed tooth received a high number of correct answers. One statistically significant association between years of experience and recommended treatment at the site of the injury in the case an avulsed tooth (KH2 = 9.384, P = 0.009). In conclusion, this survey showed appropriate knowledge of dental avulsion management and its prevention among the surveyed dentists. The findings also showed that communication between dentists and the population is deficient, especially concerning practitioners of high risk and contact sports.